Performance analysis of a threshold based distributed channel allocation algorithm for cellular networks - Tulgar, Tamer; Salamah, Muhammed (Pergamon-Elsevier Science Ltd, 2009)
Rapid advances of the handheld devices and the emergence of the demanding wireless applications require the cellular networks to support the demanding user needs more effectively. The cellular networks are expected to provide these services under a limited bandwidth. Efficient management of the wireless channels by effective channel allocation algorithms is crucial for the performance of any cellular system. To provide a better channel usage performance, dynamic channel allocation schemes have been proposed. Among these schemes, distributed dynamic channel allocation approaches showed good performance results. The two important issues that must be carefully addressed in such algorithms are the efficient co-channel interference avoidance and messaging overhead reduction. In this paper, we focus on our new distributed channel allocation algorithm and evaluate its performance through extensive simulation studies. The performance evaluation results obtained under different traffic load and user mobility conditions, show that the proposed algorithm outperforms other algorithms recently proposed in the literature. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Distributed channel allocation; Resource management; Cellular mobile networks; User mobility